Pengembangan LKPD Berbasis Science Technology Engineering Art Mathematic (STEAM) Terintegrasi Etnomatematika dengan Materi Pecahan untuk Meningkatkan Hasil Belajar Kognitif Siswa Kelas IV Sekolah Dasar - Puspita Sari Imelda; Neza Agusdianita; Abdul Muktadir (UNIB Press, 2026)
This study aims to develop, validate, and evaluate the effectiveness of a Science, Technology, Engineering, Art, and Mathematics (STEAM)-based student worksheet (LKPD) integrated with ethnomathematics to improve the cognitive learning outcomes of fourth-grade elementary school students on fractions. This research employed a Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. Data were collected through interviews, questionnaires, observations, and tests. The instruments used included a needs analysis instrument, expert validation sheets, test item validation sheets, and a product effectiveness test instrument. Data analysis techniques involved expert validity analysis, inter-rater agreement, instrument standardization, descriptive statistics, and N-Gain analysis. The results indicated that the LKPD achieved high validity, with material experts scoring 1.00, language experts scoring 0.83–1.00, and design experts scoring 1.00. User responses from teachers and students were highly positive. Posttest results showed that students achieved scores above the minimum mastery criteria, and the N-Gain score of 92.35 categorized the LKPD as highly effective. In conclusion, the STEAM-based LKPD integrated with ethnomathematics is valid, feasible, and effective in enhancing students’ cognitive learning outcomes on fractions.